Effects of kynurenic acid on cardiovascular system - Piotr Kozłowski; Magdalena Kozłowska; Karolina Kozłowska (Kazimierz Wielki University, 2017)
Kynurenic Acid (KYNA) is an endogenous metabolite of tryptophan (TRP) which is produced by aminotransferase KAT I and KAT II in the central nervous system and peripheral tissues. Moreover it has been shown that it can be supplied with food. KYNA is an antagonist of glutamate receptors NMDA and antagonist of acetylcholine α7. As we know KYNA can not penetrate or penetrates in very small amounts through the blood-brain barier. Several studies have demonstrated that kynurenine metabolism plays an important role in many neurodegenerative diseases and psychiatric disorders (Parkinson's disease, Huntington's disease, Alzheimer's disease, amyotrophic lateral sclerosis, multiple sclerosis, depression, schizophrenia). Less is known about a peripheral KYNA. Studies suggest that KYNA may have antiatherosclerotic activity and many other beneficial effects on cardiovascular system.